Penerapan Ilmu Manajemen Keuangan untuk Meningkatkan Pendapatan Masyarakat Melalui Pemberdayaan Ekonomi di Desa Ciwalat Kecamatan Pabuaran Kabupaten Sukabumi - Waruwu, Nofirman Yantoni; Utomo, Widodo Budi; Andica, Juita; Sari, Nurmala; Yaqin, Nurul; Marjohan, Masno; Hamsinah, Hamsinah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This service is entitled Application of Financial Management Science to Increase Community Income Through Economic Empowerment in Ciwalat Village, Pabuaran District, Sukabumi Regency. The general aim of this community service activity is to provide practical training and knowledge of financial management in increasing community income through economic empowerment which has an impact on community welfare. The methods used are survey methods and direct delivery of material as well as simulations and discussions regarding management, financial management, product marketing and the application of HRM in increasing community income through economic empowerment which has an impact on community welfare. The conclusion of this community service is that management assistance will be provided in developing community knowledge to increase income through economic empowerment by establishing financial management through family financial reports in an effort to realize the welfare of the people of Ciwalat Village, Pabuaran District, Sukabumi Regency.